(untitled) (International Research Journal of Management and Social Sciences, 2023)
The purpose of this experimental study was to find out Effects of 5E’s Instructional Model on Academic Achievement in 10th Grade Chemistry. The research design was true experimental in nature, based on the pre-test, post-test equivalent group design. The population of the study was comprised of all the students (boys) of 10th class studying at secondary level which were administered by Federal Directorate of Education, Islamabad. The sample of the study was consisted of 80 students taken from one boys’ school by simple random sampling technique. The sample was further divided into two equal groups by equating them on pre-test scores. One was served as control group while the other as experimental group. The experimental group was taught by 5E’s instructional model while control group by traditional teaching method. After the completion of eight weeks’ treatment, post-test was administered to both the groups. At the end, data were collected and analyzed. Mean, standard deviation and t-test were used for data analysing. Data were analyzed by applying t-test at .05 level of significance. The major findings of the study were that the overall academic achievements of experimental group in post-test taught with 5E’s instructional model enhanced significantly as compared to control group. The study also found significant increase in different aspects of cognitive domain of students’ learning; knowledge, application, comprehension and skill development abilities of experimental group taught with 5E’s instructional model.